Constructing Domains in Visual Narratives: Structural Patterns of Incongruity Resolution. - KLOMBERG, BIEN; SCHILPEROORD, JOOST; COHN, NEIL (Journal of Comparative Literature & Aesthetics)
Understanding visual narrative sequences, like those in comics, requires readers to track situational information like the continuity of characters, locations, or events across panels. Yet, some sequences intentionally present incongruities, which may elicit the inference that the narrative presents two separate domains: an established, expected storyworld (primary domain) and an additional context surrounding the incongruous events (auxiliary domain), like a character's imagination, dreams, or memories. This paper describes how these inferences are supported by visual constructional patterns, which emerge across a wide range of narratives, yielding further insight into the fundamental role of graphic and structural cues within visual storytelling.